Ethylene-vinyl alcohol copolymer resin composition, film and multilayer structure
By adding a metal compound to the ethylene-vinyl alcohol-based copolymer resin composition, which increases the second virial coefficient, the film achieves superior gas barrier properties, particularly oxygen barrier properties, under high humidity conditions.
Patent Information
- Application Number
- JP2021539267
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-11-29
- Filing Date
- 2020-08-07
- Publication Date
- 2025-04-30
- Estimated Expiration
- 2040-08-07
AI Technical Summary
Ethylene-vinyl alcohol-based copolymer films exhibit insufficient gas barrier properties, particularly oxygen barrier properties, under high humidity conditions.
Incorporating a metal compound into the ethylene-vinyl alcohol-based copolymer resin composition, where the second virial coefficient of the composition is greater than that of the pure copolymer, enhances gas barrier properties under high humidity.
The film made from this composition demonstrates excellent gas barrier properties, specifically oxygen barrier properties, even under high humidity conditions, with an oxygen permeability of 15cc·20μm/m²·day·atm or less at 20°C and 90%RH.
Smart Images

Figure 0007669928000001
Abstract
Description
[Technical field]
[0001] The present invention relates to an ethylene-vinyl alcohol copolymer resin composition, and more particularly to an ethylene-vinyl alcohol copolymer resin composition from which a film having high gas barrier properties can be obtained under high humidity conditions. [Background technology]
[0002] Ethylene-vinyl alcohol copolymers have excellent transparency, gas barrier properties such as oxygen and other gases, aroma retention, solvent resistance, oil resistance, mechanical strength, etc., and are formed into films, sheets, bottles, etc. and are widely used as various packaging materials such as food packaging materials, pharmaceutical packaging materials, industrial chemical packaging materials, and agricultural chemical packaging materials.
[0003] However, since ethylene-vinyl alcohol copolymers have relatively active hydroxyl groups in their molecules, they are highly susceptible to the effects of humidity, and their gas barrier properties decrease significantly in high humidity environments.
[0004] Patent Document 1 discloses an ethylene-vinyl alcohol copolymer film in which an inorganic compound is uniformly dispersed in an ethylene-vinyl alcohol copolymer, as an ethylene-vinyl alcohol copolymer film having improved gas barrier properties.
[0005] Furthermore, Patent Document 2 discloses an ultraviolet ray shielding film having excellent transparency, which is obtained by satisfactorily dispersing ultrafine zinc oxide particles in an ethylene-vinyl alcohol copolymer. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] International Publication No. 2016 / 088862 [Patent Document 2] JP 2004-91521 A DISCLOSURE OF THEINVENTION [Problem to be solved by the invention]
[0007] However, although the film disclosed in Patent Document 1 improves the gas barrier property by dispersing an inorganic compound in an ethylene-vinyl alcohol copolymer, the gas barrier property under high humidity conditions is insufficient, and further improvement is required. In addition, although Patent Document 2 provides a film containing zinc oxide ultrafine particles in an ethylene-vinyl alcohol copolymer, the gas barrier property under high humidity conditions is insufficient because the film does not address the issue of improving the gas barrier property under high humidity conditions, and further improvement is required.
[0008] In view of the above, the present invention provides an ethylene-vinyl alcohol copolymer resin composition having excellent gas barrier properties under high humidity, particularly excellent oxygen barrier properties under high humidity. [Means for solving the problem]
[0009] However, the present inventors have found that an ethylene-vinyl alcohol copolymer resin composition has excellent gas barrier properties under high humidity conditions when it contains a metal compound and the second virial coefficient of the ethylene-vinyl alcohol copolymer resin composition is larger than the second virial coefficient of the ethylene-vinyl alcohol copolymer contained in the ethylene-vinyl alcohol copolymer resin composition.
[0010] That is, a first aspect of the present invention is an ethylene-vinyl alcohol-based copolymer resin composition containing an ethylene-vinyl alcohol-based copolymer (X) and a metal compound, the ethylene-vinyl alcohol-based copolymer resin composition satisfying the following formula (1): ΔA2=A2-A 2,0 >0 (1) (A2 above represents the second virial coefficient when the ethylene-vinyl alcohol copolymer resin composition is subjected to static light scattering measurement using hexafluoroisopropanol as a solvent, and A 2,0 Similarly, represents the second virial coefficient of the ethylene-vinyl alcohol copolymer (X) in the ethylene-vinyl alcohol copolymer composition. A second aspect of the present invention is a film containing the ethylene-vinyl alcohol copolymer resin composition according to the first aspect, and a third aspect of the present invention is a multilayer structure having at least one layer made of the film according to the second aspect. Effect of the Invention
[0011] The ethylene-vinyl alcohol copolymer resin composition of the present invention is an ethylene-vinyl alcohol copolymer resin composition containing an ethylene-vinyl alcohol copolymer (X) and a metal compound, and satisfies the above formula (1). Therefore, when ethylene-vinyl alcohol copolymer molecules or water molecules are present around the metal compound, layers of the metal compound peel off from each other, and these fine layered structural units interact with the ethylene-vinyl alcohol copolymer at the molecular level, resulting in a film made of this ethylene-vinyl alcohol copolymer resin composition having excellent gas barrier properties, particularly oxygen barrier properties, under high humidity.
[0012] When the content of the metal compound in terms of metal is 0.01 to 10 parts by weight based on 100 parts by weight of the ethylene-vinyl alcohol copolymer (X), the resulting film can have excellent gas barrier properties, particularly oxygen barrier properties, under high humidity conditions.
[0013] A film containing the ethylene-vinyl alcohol copolymer resin composition of the present invention can have excellent gas barrier properties, particularly oxygen barrier properties, under high humidity conditions.
[0014] The oxygen permeability of the above film at 20℃ and 90% RH is 15cc·20μm / m 2When the humidity is 100% or less, the gas barrier property, particularly the oxygen barrier property, can be improved under high humidity conditions.
[0015] A multilayer structure having at least one layer made of the above film can have excellent gas barrier properties, particularly oxygen barrier properties, under high humidity conditions. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] Hereinafter, the embodiments of the present invention will be described in detail, but the present invention is not limited to these. In the present invention, the "ethylene-vinyl alcohol copolymer" may be referred to as "EVOH."
[0017] The EVOH resin composition of the present invention contains EVOH (X) and a metal compound. Each component will be described below.
[0018] [EVOH(X)] The EVOH (X) is a resin obtained by saponifying an ethylene-vinyl ester copolymer, which is a copolymer of ethylene and a vinyl ester monomer, and is a water-insoluble thermoplastic resin.
[0019] The polymerization of ethylene and vinyl ester monomers can be carried out by any known polymerization method, such as solution polymerization, suspension polymerization, or emulsion polymerization, and generally, solution polymerization using methanol as a solvent is used. The saponification of the obtained ethylene-vinyl ester copolymer can also be carried out by a known method.
[0020] The EVOH (X) thus produced is mainly composed of structural units derived from ethylene and vinyl alcohol structural units, and usually contains a small amount of vinyl ester structural units that remain unsaponified.
[0021] As the vinyl ester monomer, vinyl acetate is typically used because of its good market availability and efficiency in treating impurities during production. Other vinyl ester monomers include, for example, aliphatic vinyl esters such as vinyl formate, vinyl propionate, vinyl valerate, vinyl butyrate, vinyl isobutyrate, vinyl pivalate, vinyl caprate, vinyl laurate, vinyl stearate, and vinyl versatate, and aromatic vinyl esters such as vinyl benzoate. Usually, aliphatic vinyl esters having 3 to 20 carbon atoms, preferably 4 to 10 carbon atoms, and particularly preferably 4 to 7 carbon atoms can be used. These can be used alone or in combination of two or more kinds.
[0022] The content of the ethylene structural unit in the EVOH (X) can be controlled by the ethylene pressure when the vinyl ester monomer and ethylene are copolymerized, and is usually 20 to 60 mol%, preferably 25 to 50 mol%, particularly preferably 25 to 35 mol%. If the content is too low, the gas barrier property and melt moldability under high humidity tend to decrease, and conversely, if it is too high, the gas barrier property tends to decrease. The content of the ethylene structural unit can be measured based on ISO14663.
[0023] The degree of saponification of the vinyl ester component in EVOH (X) can be controlled by the amount, temperature, time, etc. of the saponification catalyst (usually an alkaline catalyst such as sodium hydroxide is used) used when saponifying the ethylene-vinyl ester copolymer, and is usually 90 to 100 mol%, preferably 95 to 100 mol%, particularly preferably 99 to 100 mol%. If the degree of saponification is too low, the gas barrier properties, thermal stability, moisture resistance, etc. tend to decrease. The degree of saponification of EVOH(X) can be measured based on JIS K6726 (wherein EVOH(X) is used as a solution uniformly dissolved in a water / methanol solvent).
[0024] The melt flow rate (MFR) of the EVOH (X) (210°C, load 2160 g) is usually 0.5 to 100 g / 10 min, preferably 1 to 50 g / 10 min, and particularly preferably 3 to 35 g / 10 min. If the MFR is too high, the film formability tends to be unstable, and if it is too low, the viscosity tends to be too high, making melt extrusion difficult. The MFR is an index of the degree of polymerization of EVOH, and can be adjusted by the amount of polymerization initiator and the amount of solvent used when copolymerizing ethylene with a vinyl ester monomer.
[0025] In addition, EVOH (X) may further contain structural units derived from the comonomers shown below within a range that does not impair the effects of the present invention (for example, 10 mol % or less of EVOH (X)). Examples of the comonomers include olefins such as propylene, 1-butene, and isobutene; hydroxyl-containing α-olefins such as 3-buten-1-ol, 3-butene-1,2-diol, 4-penten-1-ol, and 5-hexene-1,2-diol, as well as their esterified and acylated derivatives; hydroxyalkylvinylidenes such as 2-methylenepropane-1,3-diol and 3-methylenepentane-1,5-diol; 1,3-diacetoxy-2-methylenepropane, 1,3-dipropionyloxy-2-methylenepropane, and 1,3-dibutyryloxy. -Hydroxyalkylvinylidene diacetates such as 2-methylenepropane; unsaturated acids such as acrylic acid, methacrylic acid, crotonic acid, (anhydrous) phthalic acid, (anhydrous) maleic acid, (anhydrous) itaconic acid, or their salts or mono- or dialkyl esters in which the alkyl group has 1 to 18 carbon atoms; acrylamide, N-alkylacrylamide in which the alkyl group has 1 to 18 carbon atoms, N,N-dimethylacrylamide, 2-acrylamidopropanesulfonic acid or its salts, acrylamidopropyldimethylamine or its acid salts or its quaternary salts, etc. acrylamides such as methacrylamide, N-alkyl methacrylamides in which the alkyl group has 1 to 18 carbon atoms, N,N-dimethyl methacrylamide, 2-methacrylamidopropanesulfonic acid or its salt, methacrylamidepropyldimethylamine or its acid salt or its quaternary salt, and other methacrylamides; N-vinylpyrrolidone, N-vinylformamide, N-vinylacetamide, and other N-vinylamides; vinyl cyanides such as acrylonitrile and methacrylonitrile; alkyl vinyl ethers in which the alkyl group has 1 to 18 carbon atoms, hydrochloride, etc. vinyl ethers such as alkoxyalkyl vinyl ether and alkoxyalkyl vinyl ether; halogenated vinyl compounds such as vinyl chloride, vinylidene chloride, vinyl fluoride, vinylidene fluoride and vinyl bromide; vinyl silanes such as trimethoxyvinylsilane; halogenated allyl compounds such as allyl acetate and allyl chloride; allyl alcohols such as allyl alcohol and dimethoxyallyl alcohol; and comonomers such as trimethyl-(3-acrylamido-3-dimethylpropyl)-ammonium chloride and acrylamido-2-methylpropanesulfonic acid.These can be used alone or in combination of two or more.
[0026] In particular, EVOH (X) having a primary hydroxyl group in the side chain is preferred because it has good secondary formability while maintaining gas barrier properties. Among these, EVOH copolymerized with a hydroxyl group-containing α-olefin is preferred, and EVOH having a 1,2-diol structure in the side chain is particularly preferred. In particular, in the case of EVOH having a primary hydroxyl group in the side chain, the content of the structural unit derived from the monomer having the primary hydroxyl group is usually 0.1 to 20 mol %, preferably 0.5 to 15 mol %, and particularly preferably 1 to 10 mol % of EVOH (X).
[0027] The EVOH (X) used in the present invention may be "post-modified" such as urethanized, acetalized, cyanoethylated, oxyalkylated, or acylated.
[0028] Furthermore, the EVOH (X) used in the present invention may be a mixture with different other EVOHs. Examples of such other EVOHs include those having a different degree of saponification, a different degree of polymerization, and a different copolymerization component.
[0029] The EVOH (X) is preferably the main component of the EVOH resin composition, and the content of the EVOH (X) in the entire EVOH resin composition is usually 80% by weight or more, preferably 90% by weight or more, and particularly preferably 95% by weight or more. The upper limit is usually 99.99% by weight.
[0030] <Metal compounds> The metal compound used in the present invention preferably has a structure in which specific structural units are arranged in layers with specific interplanar spacing.
[0031] The structural unit contains a metal, a hydroxy ligand, and an anionic ligand other than a hydroxy ligand, and is preferably represented by the following chemical formula (i). M a (OH) b Y n-(2a-b) / n (i) (The above M represents a metal species, and Y represents an anionic ligand other than a hydroxyl ligand having a valence of n-. However, Y does not include O (oxo ligand). n is an integer of 1 or more, and a and b are numbers greater than 0, and a / b=0.1 to 10 is satisfied.)
[0032] In the above chemical formula (i), examples of M include Na, K, Ca, Ti, Cr, Mn, Fe, Co, Ni, Cu, and Zn. These metal species may be contained alone or in combination. Among them, Ni, Co, and Zn are particularly preferred, and Zn is particularly preferred, in terms of excellent oxygen barrier properties under high humidity conditions.
[0033] In the above chemical formula (i), examples of Y include RO (alkoxy ligand), ROCO (carboxylic acid ligand), NO3, SO3, PO4, BO3, F, Br, Cl, etc. (R is an alkyl chain, C m H 2m+1 It is generally represented by a chemical formula in which m=1 to 20. However, the alkyl chain may have a functional group such as an OH group, so long as it does not impair the effects of the present invention. However, O (oxo ligand) is excluded as Y. These anionic ligands may be contained alone or in combination of two or more kinds. Among them, from the viewpoint of the interaction with EVOH (X), NO3, Cl, RO, and ROCO are preferred, ROCO is particularly preferred, and among them, CHOCO is particularly preferred.
[0034] The metal compounds used in the present invention exclude common clay minerals such as gibnite, kaolinite, illite / mica, smectite, vermiculite, chlorite, iron compounds, quartz, amorphous minerals, and carbonate minerals.
[0035] The metal compound used in the present invention may contain water molecules, and the water content is usually 0.1 to 20% by weight.
[0036] Specific examples of the metal compound include layered compounds containing Zn as a metal species. Among them, the Zn-containing layered compound represented by the chemical formula [Zn5(OH)8(CH3CO2)2·2H2O] is preferred because of its excellent oxygen barrier properties under high humidity conditions.
[0037] The metal compound can be obtained, for example, by reacting a metal-containing compound under specific conditions. The metal species contained in the metal-containing compound include the metal species described for M in the above chemical formula (i), and among them, Ni, Co, and Zn are preferred, and Zn is more preferred.
[0038] Examples of the metal-containing compound include organic acid metal salts and inorganic metal salts.
[0039] Examples of organic acids constituting the organic acid metal salt include monovalent carboxylic acids such as acetic acid, divalent carboxylic acids such as succinic acid, oxalic acid, and tartaric acid, and trivalent or higher carboxylic acids such as citric acid and ethylenediaminetetraacetic acid. These may be used alone or in combination of two or more. The organic acid metal salt may be a hydrate or an anhydride. As the organic acid metal salt, a monovalent carboxylate metal salt is preferred from the viewpoint of excellent oxygen barrier properties under high humidity conditions, a metal acetate salt is particularly preferred, and zinc acetate or a hydrate thereof is particularly preferred.
[0040] Examples of the inorganic metal salt include metal fluorides, chlorides, bromides, iodides, and oxoacids. These may be used alone or in combination of two or more. The inorganic metal salt may be a hydrate or an anhydride. As the inorganic metal salt, metal chlorides and oxoacids are preferred from the viewpoint of excellent oxygen barrier properties under high humidity conditions, and zinc chloride, zinc nitrate, or hydrates thereof are particularly preferred.
[0041] The metal compound used in the present invention can be obtained by using the above-mentioned metal-containing compound, for example, by (I) a method of reacting a metal-containing compound in the presence of a base, or (II) a method of reacting a metal-containing compound by heating. Each method will be described in detail below.
[0042] [Method (I)] The above method (I) is a method in which a metal-containing compound is reacted in the presence of a base.
[0043] Examples of the base used in the above method (I) include hydroxides of alkali metals or alkaline earth metals. Among them, hydroxides of alkali metals are preferred, and sodium hydroxide is particularly preferred, because they have excellent reactivity with metal-containing compounds.
[0044] In the reaction of the metal-containing compound with the base, the metal-containing compound and the base may be mixed in a solution and reacted. From the viewpoint of workability, EVOH (X) may be dissolved in the solution. The method of mixing the metal-containing compound and the base is not particularly limited, and examples thereof include a method of mixing a solution in which a metal-containing compound is dissolved with a solution in which a base is dissolved, and a method of mixing a slurry liquid in which a metal-containing compound is dispersed with a solution in which a base is dissolved. Among these, from the viewpoint of reaction efficiency, a method of mixing a solution in which a metal-containing compound is dissolved with a solution in which a base is dissolved is preferred. Furthermore, when an organic acid metal salt is used as the metal-containing compound, a method of adding a solution in which an organic acid metal salt is dissolved to a solution in which a base is dissolved and mixing them is preferred, and when an inorganic metal salt is used, a method of adding a solution in which a base is dissolved to a solution in which an inorganic metal salt is dissolved and mixing them is preferred.
[0045] The solvent for dissolving or dispersing the metal-containing compound and the base is not particularly limited as long as it can dissolve or disperse the metal-containing compound and the base, and examples thereof include water, methanol, ethanol, 1-propanol, 2-propanol, 1-butanol, 2-butanol, and other lower alcohols having 1 to 5 carbon atoms. These may be used alone or in combination of two or more. Among these, water is preferred from the viewpoint of ease of post-treatment.
[0046] The concentration of the metal-containing compound in the solution in which the metal-containing compound is dissolved or dispersed is usually 0.5 to 3 mol / L, and preferably 1 to 2 mol / L. The concentration of the base in the solution obtained by dissolving the base in the solvent is usually 0.01 to 100 mol / L, preferably 0.1 to 30 mol / L, and particularly preferably 1 to 10 mol / L. If the concentrations of the metal-containing compound and the base are lower than the above ranges, the reaction tends not to proceed sufficiently, whereas if the concentrations of the metal-containing compound and the base are higher than the above ranges, side reactions tend to occur.
[0047] The molar ratio of the metal-containing compound to the base (metal-containing compound:base) is usually 0.5:2 to 2:0.5, preferably 0.8:1.5 to 1.5:0.8, and particularly preferably 0.9:1.2 to 1:1. If the molar ratio is outside the above range, the reaction tends not to proceed sufficiently.
[0048] The pH when reacting the metal-containing compound with the base is usually 4 to 9, preferably 5 to 8. If the pH is too low compared to the above range, the reaction tends not to proceed sufficiently. If the pH is too high compared to the above range, the generated metal compound tends to decompose. The pH is adjusted by adjusting the amount of the solution in which the metal-containing compound is dissolved or the slurry in which the metal-containing compound is dispersed, and the solution in which the base is dissolved.
[0049] The reaction temperature in the above reaction is usually 15 to 60° C., and preferably 20 to 40° C. If the reaction temperature is too low, the reaction tends not to proceed sufficiently, whereas if the reaction temperature is too high, the metal-containing compound tends to be decomposed by heat, and the target metal compound tends not to be obtained. The reaction time is usually 0.5 to 5 hours, and preferably 1 to 3 hours, and the reaction may be carried out under normal pressure.
[0050] After the above reaction, a metal compound is obtained. The obtained metal compound may be used as it is, but it is preferable to purify the metal compound by washing, pulverization, or the like before use.
[0051] [Method (II)] The above method (II) is a method in which a metal-containing compound is reacted by heating.
[0052] The above method (II) is usually carried out by heating a solution in which a metal-containing compound is dissolved while stirring. From the viewpoint of workability, EVOH (X) may be dissolved in the above solution.
[0053] As the solvent for dissolving the metal-containing compound, the solvents listed in the above method (I) can be used. Among them, water and alcohols are preferable, and a mixed solvent of water and 1-propanol is particularly preferable.
[0054] As for the heating conditions, the solution may be heated to a temperature of usually 20 to 100° C., preferably 50 to 95° C., and particularly preferably 70 to 90° C. If the reaction temperature is too low, the reaction tends not to proceed sufficiently, whereas if the reaction temperature is too high, the metal-containing compound tends to be decomposed by heat, and the target metal compound tends not to be obtained. The reaction time is usually 0.1 to 100 hours, preferably 0.5 to 30 hours, and particularly preferably 1 to 10 hours, and the reaction may be carried out under normal pressure.
[0055] After the above reaction, a metal compound is obtained. The obtained metal compound may be used as it is, or may be purified by washing, pulverization, or the like before use.
[0056] Generally, a metal compound refers to, for example, a metal salt, a metal oxide, a metal complex, a simple metal, or an alloy, but the metal compound obtained by each of the above methods is a metal layered compound having a structure in which the layered structural units represented by the above chemical formula (i) are layered at a specific interplanar spacing, as described above. Therefore, when EVOH molecules or water molecules are present around the metal compound, the layers of the metal compound are peeled off, and the peeled fine layered structural units interact with EVOH at the molecular level, resulting in excellent oxygen barrier properties.
[0057] In terms of excellent gas barrier properties, particularly oxygen barrier properties, under high humidity, the metal compound used in the present invention preferably has a main X-ray diffraction peak at 2θ=2 to 15°, more preferably at 2θ=2 to 9°, and particularly preferably at 2θ=3 to 8°, when measured by wide-angle X-ray diffraction using CuKα radiation. When the main X-ray diffraction peak is in the above range, the metal compound and EVOH (X) interact to increase the polarity of EVOH (X), resulting in excellent oxygen barrier properties under high humidity.
[0058] The interlayer distance (distance between layers) of the metal compound is preferably 0.01 to 50 nm, more preferably 0.1 to 30 nm, from the viewpoint of interaction with EVOH (X) molecules and water molecules. The interlayer distance of the metal compound can be calculated from the Bragg formula based on the diffraction position of the strongest peak in the range of 2θ=2 to 15° when analyzed by X-ray diffraction.
[0059] The wide-angle X-ray diffraction is measured under the following conditions. [Measurement conditions] Equipment used: D8 DISCOVER (manufactured by Bruker Japan) Detector: 2D detector VANTEC-500 (manufactured by Bruker Japan) Voltage: 50kV ·Current: 100mA Camera length: 100mm ·Measurement method: Reflection method Accumulation time: 30 minutes Wavelength: CuKα radiation (Kα1 and Kα2 are not separated) Detector position: 2θ=10° ·X-ray incident angle: θ=0.3° ·Conditions for one-dimensionalization in the 2θ direction: 2θ=0~35°, azimuth angle (chi)=-95~-85° ·Azimuth direction one-dimensional: Azimuth angle (chi)=-180~0° When the diffraction peak is one-dimensionalized in the azimuth direction, the diffraction peak is one-dimensionalized in the range of 1.0° so that the peak with the strongest diffraction intensity is included in the range of 2θ=2 to 15°. In this case, if a peak is observed in the range of azimuth angles -180 to 0°, it is determined that the diffraction peak is observed in the range of 2θ=2 to 15°. For example, if a diffraction peak is observed at 2θ=6.8°, when the diffraction peak is one-dimensionalized in the azimuth direction in the range of 2θ=6.0 to 7.0°, if a peak is observed in the range of azimuth angles = -180 to 0°, it may be determined that the diffraction peak is observed in the range of 2θ=2 to 15°.
[0060] As a sample to be used for the wide-angle X-ray diffraction, the EVOH resin composition in the form of a film described below may be used as it is. In addition, when the film of the EVOH resin composition is laminated with another substrate, if the EVOH resin composition layer can be peeled off, the EVOH resin composition layer is peeled off and measurement is performed, and if the EVOH resin composition layer cannot be peeled off, the measurement may be performed while the film is laminated with the other substrate. Note that the thickness of the EVOH resin composition layer (film) at the time of measurement is preferably 30 μm or more, and if the film is not thick enough, a film may be laminated.
[0061] The molecular weight of the layered structural unit peeled off from the metal compound is preferably from 100 to 10,000, particularly preferably from 200 to 2,000, in view of the possibility of interaction at the molecular level of EVOH (X).
[0062] Moreover, the layered structural unit is preferably hydrophilic in terms of interaction with the molecules of EVOH (X). Furthermore, it is preferable that the layered structural unit does not decompose even when left to stand for 1,000 hours in an environment of 20° C. and 90% RH.
[0063] The content of the metal compound in the EVOH resin composition in terms of metal is usually 0.01 to 10 parts by weight, preferably 0.05 to 8 parts by weight, particularly preferably 0.1 to 5 parts by weight, and particularly preferably 0.2 to 3 parts by weight, based on 100 parts by weight of EVOH (X). If the content of the metal compound is too low, the oxygen barrier property under high humidity conditions tends to decrease, whereas if the content of the metal compound is too high, whitening and reduced transparency tend to occur when the composition is made into a film or the like. When the EVOH resin composition contains a plurality of metal compounds each having a different metal species, the total amount of all the metal compounds contained in the EVOH resin composition is defined as the content. The content of the metal compounds can be determined by the standard addition method using ICP-MS.
[0064] The EVOH resin composition can be obtained by mixing EVOH (X), a metal compound, and, if necessary, other components.
[0065] [Other ingredients] The above other components can be used within a range that does not impair the effects of the present invention, and examples of the components that are generally added to EVOH resin compositions include heat stabilizers, antioxidants, antistatic agents, colorants, ultraviolet absorbers, lubricants, plasticizers, light stabilizers, surfactants, antibacterial agents, desiccants, antiblocking agents, flame retardants, crosslinking agents, curing agents, foaming agents, crystal nucleating agents, antifogging agents, biodegradable additives, silane coupling agents, oxygen absorbers, etc. These can be used alone or in combination of two or more kinds.
[0066] <EVOH resin composition> The EVOH resin composition of the present invention contains the above EVOH (X) and a metal compound, and is characterized by satisfying the following formula (1). ΔA2 = A2 - A 2,0 >0 ···(1) (Wherein A2 represents the second virial coefficient when static light scattering measurement of the above EVOH resin composition is performed using hexafluoroisopropanol as a solvent, and A 2,0 represents the second virial coefficient of EVOH (X) in the above EVOH resin composition.)
[0067] The above A2 and A 2,0 are obtained as follows. Using hexafluoroisopropanol as a solvent, five solutions with a solid content concentration range of 0.1 to 1 mg / mL of the EVOH resin composition are prepared, static light scattering measurement is performed at a temperature of 25°C, and the second virial coefficient A2 and weight average molecular weight Mw of the EVOH resin composition obtained from the Zimm plot b are determined. Also, the second virial coefficient A of EVOH (X) is determined by the same method x and the weight average molecular weight Mw a are determined. Note that the above EVOH (X) is the same as the EVOH (X) contained in the EVOH resin composition, that is, the EVOH before the EVOH resin composition contains a metal compound. Since the EVOH resin composition of the present invention contains EVOH (X) and a metal compound, the weight average molecular weight of EVOH (X) in the EVOH resin composition is different from the apparent weight average molecular weight (Mw a ) of EVOH (X), and the second virial coefficient A x obtained by static light scattering measurement of EVOH (X) cannot be taken as the second virial coefficient A 2,0 of EVOH (X) in the EVOH resin composition. Therefore, the second virial coefficient A 2,0 of EVOH (X) in the EVOH resin composition is determined by the following procedure. 1) Calculate the constant q from the following equation (2). q=A X / Mw a v (2) A x : Second virial coefficient obtained by static light scattering measurement of EVOH(X) Mw a Weight average molecular weight of EVOH(X) obtained by static light scattering measurement ν :-0.25 Here, since ν in a good solvent is usually −0.25, the calculation is performed assuming ν=−0.25. 2) The constant q thus obtained and the weight average molecular weight Mw obtained by static light scattering measurement of the EVOH resin composition b Using the above, the second virial coefficient A of EVOH (X) in the EVOH resin composition is calculated from the following formula (3): 2,0 Note that the following v is -0.25, the same as in formula (2). A 2,0 =q × Mw b v (3)
[0068] In the present invention, in order to have excellent oxygen barrier properties under high humidity, it is necessary that ΔA2 is greater than 0 (ΔA2>0). Preferably, ΔA2>0.00005, more preferably ΔA2>0.0001, and particularly preferably ΔA2>0.0005. The upper limit is usually 0.1, and preferably 0.01.
[0069] The second virial coefficient indicates the affinity between the polymer chain and the solvent. In the EVOH resin composition of the present invention, the second virial coefficient of the EVOH resin composition is greater than the second virial coefficient of EVOH (X) in the EVOH resin composition, so that the polymer chain of the EVOH resin composition has a greater affinity with hexafluoropropanol than EVOH (X). In other words, the EVOH resin composition of the present invention, which has a high affinity with hexafluoropropanol, a highly polar solvent, has a higher polarity than EVOH (X). Therefore, the EVOH resin composition of the present invention has the effect of having excellent oxygen barrier properties under high humidity conditions.
[0070] The EVOH resin composition satisfying the above formula (1) can be obtained by allowing the EVOH resin composition to stand under high humidity. Usually, an EVOH resin composition containing EVOH(X) and a metal compound does not satisfy the above formula (1) and has only a gas barrier property comparable to that of EVOH(X) as it is.
[0071] When allowing it to stand under the above high humidity, the shape of the EVOH resin composition is not particularly limited, but it is preferably allowed to stand in the form of a film. Hereinafter, a film containing the EVOH resin composition will be described.
[0072] <Film Containing EVOH Resin Composition> The film containing the EVOH resin composition of the present invention is obtained by forming a film of the composition containing the above EVOH resin composition, and preferably, it is obtained by forming a film of the above EVOH resin composition.
[0073] Examples of the method for forming the above film include a method using a solution (coating solution) of a composition containing the EVOH resin composition, and a method of melt-molding a pellet-like composition containing the EVOH resin composition of the present invention using an extruder. Among them, a method using a solution (coating solution) of a composition containing the EVOH resin composition is preferred. Further, the solid content concentration when using the above coating solution is usually 0.5 to 30% by weight, preferably 5 to 20% by weight.
[0074] Examples of the preparation of the above coating solution include a method of charging all components into a solvent at once and mixing them, and a method of adding and mixing other components to a solution in which some components are dissolved in a solvent. Among them, from the viewpoint of workability, a method of adding and mixing other components to a solution in which EVOH(X) is dissolved in a solvent is preferred. In addition, in the method for obtaining the above-mentioned metal compound, it is also preferable to dissolve EVOH(X) in a solvent when reacting a metal-containing compound, and it is particularly preferable when obtaining a metal compound by the method (II) from the viewpoint of workability. As the solvent, the solvents exemplified for the metal compound can be used.
[0075] The film-forming method may be a known method such as a melt extrusion method, an endless belt method, a drum method, a casting method such as a coating method, etc. Among these, the casting method is preferred, and the coating method is more preferred.
[0076] Examples of the coating method include known methods such as bar coating, roll coating, die coating, gravure coating, comma coating, and screen printing.
[0077] After the film formation, a film made of the EVOH resin composition can be obtained by drying, for example, by heat treatment at 60 to 105° C. for 0.5 to 10 minutes. Furthermore, the above film may be subjected to a stretching operation such as uniaxial stretching or biaxial stretching, if necessary.
[0078] The film may be a single layer structure or a multilayer structure, but is preferably a multilayer structure. The multilayer structure preferably has at least one layer made of the film. The multilayer structure may be formed by laminating the film formed, or may be laminated with another base resin.
[0079] The thickness of the film is usually 1 to 200 μm, preferably 1 to 100 μm, and particularly preferably 1 to 50 μm. When the formed film has a multi-layer structure, the thickness of the film is the total thickness of all the films made of the EVOH resin composition.
[0080] Examples of the base resin include polyethylene-based resins such as linear low-density polyethylene, low-density polyethylene, very low-density polyethylene, medium-density polyethylene, high-density polyethylene, ethylene-propylene (block and random) copolymers, and ethylene-α-olefin (α-olefin having 4 to 20 carbon atoms) copolymers; polypropylene-based resins such as polypropylene and propylene-α-olefin (α-olefin having 4 to 20 carbon atoms) copolymers; (unmodified) polyolefin-based resins such as polybutene, polypentene, and polycyclic olefin-based resins (polymers having a cyclic olefin structure in at least one of the main chain and side chain); and polyolefins obtained by treating with an unsaturated carboxylic acid or Examples of the polyolefin resin include a broad polyolefin resin including modified olefin resins such as unsaturated carboxylic acid modified polyolefin resins graft-modified with esters, ionomers, ethylene-vinyl acetate copolymers, ethylene-acrylic acid copolymers, ethylene-acrylic acid ester copolymers, polyester resins, polyamide resins (including copolymerized polyamides), polyvinyl chloride, polyvinylidene chloride, acrylic resins, polystyrene, vinyl ester resins, polyester elastomers, polyurethane elastomers, polystyrene elastomers, halogenated polyolefins such as chlorinated polyethylene and chlorinated polypropylene, aromatic or aliphatic polyketones, etc. These may be used alone or in combination of two or more. In addition, these base resins may be subjected to surface treatment such as corona treatment.
[0081] The EVOH resin composition of the present invention satisfies the formula (1), and in order to obtain an EVOH resin composition that satisfies the formula (1) as described above, a film containing the EVOH resin composition is allowed to stand under high humidity. By standing under high humidity, the EVOH resin composition satisfies the formula (1), and excellent gas barrier properties are obtained. Although the mechanism behind this is not clear, it is speculated that by standing under high humidity, the molecules of EVOH (X) are plasticized, and the metal compounds dispersed in the film interact with EVOH (X) or are localized on the surface of the film.
[0082] In the present invention, "high humidity" means 20±5° C. and 90±10% RH. The standing time is usually 70 hours or more, preferably 300 hours or more, and more preferably 600 hours or more. The upper limit of the standing time is usually 1,000 hours.
[0083] In this manner, a film containing the EVOH resin composition of the present invention is obtained.
[0084] The oxygen permeability of the film containing the EVOH resin composition is 15cc·20μm / m 2 ·day·atm(cm 3 20μm / m 2 ·day·atm) or less, and 10cc·20μm / m 2 ·day·atm or less is preferable, and 5cc·20μm / m 2 It is particularly preferable that the oxygen permeability is less than 0 cc·day·atm. Note that the oxygen permeability is measured in an environment of 20°C and 90% RH, and the lower limit of the oxygen permeability is usually 0 cc·20 μm / m 2 ·day·atm. The oxygen permeability can be determined by an oxygen permeability measuring device.
[0085] The EVOH resin composition of the present invention and a film containing the EVOH resin composition are useful as packaging materials, and can be suitably used in particular as packaging materials for foods, medicines, and the like. EXAMPLES
[0086] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples as long as it does not depart from the gist of the present invention. In the following, "parts" refers to parts by weight.
[0087] Prior to the examples, the following EVOH (X) was prepared.
[0088] [EVOH(X)] ·EVOH (X-1) [Ethylene structural unit content: 25 mol%, MFR: 4 g / 10 min, Saponification degree: 99.6 mol%, Moisture content: 0.3 wt%] ·EVOH (X-2) [Ethylene structural unit content: 44 mol%, MFR: 3 g / 10 min, Saponification degree: 99.6 mol%, Moisture content: 0.3 wt%]
[0089] Also, the synthesis of a Zn-containing layered compound, which is a metal compound, was carried out according to the following procedure.
[0090] <Synthesis of Zn-containing layered compound> The synthesis of the Zn-containing layered compound was carried out according to the method described in Inorg. Chem. 2013, 52, 95 - 102. Specifically, while stirring 900 parts of a 1.5 mol / L aqueous sodium hydroxide solution at 27°C, 900 parts of a 1.5 mol / L aqueous zinc acetate dihydrate (manufactured by Fujifilm Wako Pure Chemical Corporation) solution was added thereto, and the mixture was stirred at 27°C for 2 hours to cause a reaction. After the reaction, the precipitated white precipitate was filtered off by vacuum filtration. Then, the obtained white solid and 750 parts of water were stirred and filtered again to wash the white solid. This washing operation was performed a total of 3 times while replacing the water. Finally, the filtered white solid was dried at 60°C overnight under normal pressure to obtain a Zn-containing layered compound.
[0091] <Identification of the synthesized Zn-containing layered compound> The above Zn-containing layered compound was measured by solid NMR and wide-angle X-ray diffraction to identify the Zn-containing layered compound.
[0092] 〔Solid NMR( 13 C-CP / MAS) measurement〕 The above Zn-containing layered compound was filled into a 4 mmφ zirconia rotor, sealed with a polyethylene drive tip, and used as a measurement sample. This measurement sample was measured by solid NMR [AVANCEIII 400WB( 1 H: 400 MHz, 13 C: 100 MHz), manufactured by Bruker Japan] using a CP / MAS probe. The measurement conditions were as follows: rotation at 5000 Hz, 90° pulse width 45 μs, contact time 2 ms, accumulation count 485 times, acquisition time 50 ms, and delay time 5 seconds.
[0093] [Wide-angle X-ray diffraction (XRD) measurement] The above-mentioned compound containing Zn was subjected to wide-angle X-ray diffraction (XRD) measurement under the following conditions. [Measurement conditions] Equipment used: D8 DISCOVER (manufactured by Bruker Japan) Voltage: 50kV Current: 100mA Camera length: 150mm Measurement method: Reflection method Accumulation time: 20 minutes As a result of the measurement, the main peaks were detected at 2θ=6.8°, 13.5°, and 20.2°.
[0094] The solid-state NMR and wide-angle X-ray diffraction measurements showed that the compound was consistent with the Zn-containing layered compound described in Inorg. Chem. 2013, 52, 95-102, and therefore the compound was identified as the Zn-containing layered compound [Zn5(OH)8(CH3CO2)2·2H2O].
[0095] In addition, when the Zn-containing layered compound [Zn5(OH)8(CH3CO2)2·2H2O] was measured by wide-angle X-ray diffraction, the interlayer distance was calculated from the Bragg equation based on the diffraction position at 2θ=6.8° where the strongest peak intensity was found. As a result, the Zn-containing layered compound [Zn5(OH)8(CH3CO2)2·2H2O] was found to be a layered compound with an interlayer distance of 1.3 nm.
[0096] <Example 1> 5 parts of EVOH (X-1) were added to 45 parts of a mixed solvent of water / 1-propanol = 1 / 1 (volume ratio), and the mixture was heated and stirred at 87 ° C for 1 hour to completely dissolve EVOH (X-1). The solution was allowed to cool to 55 ° C, and 0.05 parts of the Zn-containing layered compound obtained above was added in metal equivalent to 100 parts of EVOH (X-1), and the mixture was stirred for 2 hours at 55 ° C to prepare an EVOH resin composition (coating liquid). The obtained coating liquid was applied to the corona-treated surface of a PET substrate having a thickness of 12 μm that had been corona-treated using a wire bar #24, and dried at 80 ° C for 5 minutes. This process was repeated twice to obtain a two-layer film in which a film layer having a thickness of 6 μm was laminated on the PET substrate. The obtained film was left to stand for 600 hours under humidity-controlled conditions of 20 ° C and 90% RH to prepare a film.
[0097] <Example 2> A film was prepared in the same manner as in Example 1, except that the amount of the Zn-containing layered compound added was changed to 0.1 parts in terms of metal per 100 parts of EVOH (X-1). The film was prepared under the same humidity control conditions.
[0098] <Example 3> A film was prepared in the same manner as in Example 1, except that the amount of the Zn-containing layered compound added was changed to 1.0 part in terms of metal per 100 parts of EVOH (X-1), and the film was prepared under the same humidity control conditions.
[0099] <Example 4> 5 parts of EVOH (X-2) and 1.0 part of zinc acetate dihydrate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) were added to 45 parts of a mixed solvent of water / 1-propanol = 4 / 6 (volume ratio) in terms of metal per 100 parts of EVOH (X-2), and the mixture was heated and stirred at 87 ° C (under reflux) for 2 hours to obtain an EVOH resin composition containing a metal compound (Zn-containing layered compound) obtained by reacting zinc acetate dihydrate. This solution was allowed to cool to 55 ° C to prepare a coating liquid. The obtained coating liquid was used to prepare a film in the same manner as in Example 1, and was prepared under the same humidity control conditions.
[0100] <Comparative Example 1> A film was prepared in the same manner as in Example 1, except that the Zn-containing layered compound was not added, and the film was prepared under the same humidity control conditions.
[0101] <Comparative Example 2> A film was prepared in the same manner as in Example 1, except that 0.1 parts of zinc oxide (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.) was added per 100 parts of EVOH (X-1) in terms of metal instead of the Zn-containing layered compound in Example 1, and the film was prepared under the same humidity control conditions.
[0102] <Comparative Example 3> A film was prepared in the same manner as in Example 4, and was prepared under the same humidity conditioning conditions, except that zinc acetate dihydrate was not added.
[0103] The films obtained above in Examples 1 to 4 and Comparative Examples 1 to 3 were subjected to static light scattering measurement, wide-angle X-ray diffraction measurement, and evaluation of oxygen barrier property under the following conditions. The results are shown in Table 1 below.
[0104] [Static Light Scattering Measurement of EVOH Resin Composition and EVOH(X)] Only the EVOH resin composition film was peeled off from the coating film obtained above. This EVOH resin composition film and the EVOH (X) used in the preparation were each dissolved in hexafluoroisopropanol to prepare five levels of measurement solutions with concentrations ranging from 0.1 to 1 mg / mL. Then, each measurement solution was repeatedly filtered three times with a PTFE membrane filter having a pore size of 0.2 μm. Thereafter, the filtrate was subjected to static light scattering measurement using a static light scattering photometer (Otsuka Electronics Co., Ltd., SLS-6500). The scattering angle θ was 20 to 150° at 10° intervals, and the measurement temperature was 25°C. Toluene was used for calibration of the device. The refractive index concentration increment (dn / dc) of the EVOH resin composition and EVOH (X) required for determining the weight average molecular weight and the second virial coefficient was measured using a static light scattering measurement solution with a differential refractive index meter (Otsuka Electronics Co., Ltd., DRM-3000). The measurement temperature was 25°C.
[0105] [Static light scattering analysis] A Zimm plot was created from the scattering intensity obtained by static light scattering measurement, and the weight average molecular weight (Mw b ) and the second virial coefficient A2 were calculated. The weight average molecular weight (Mw a ) and the second virial coefficient A x The second virial coefficient A of EVOH (X) in the EVOH resin composition is calculated by the above-mentioned method. 2,0 asked for. The obtained second virial coefficient A2 of the EVOH resin composition and the second virial coefficient A of EVOH (X) in the EVOH resin composition 2,0 ΔA2 was calculated from the above formula (1).
[0106] [Wide-angle X-ray diffraction (XRD) measurement of film] The EVOH resin composition film obtained above was peeled off from the PET film and laminated to a thickness of 30 μm or more to prepare a sample. Wide-angle X-ray diffraction measurement of this sample was carried out under the following conditions. [Measurement conditions] Equipment used: D8 DISCOVER (manufactured by Bruker Japan) Detector: 2D detector VANTEC-500 (manufactured by Bruker Japan) Voltage: 50kV Current: 100mA Camera length: 100mm Measurement method: Reflection method Accumulation time: 30 minutes Wavelength: CuKα radiation (Kα1 and Kα2 are not separated) Detector position: 2θ=10° X-ray incident angle: θ=0.3° Conditions for making the image one-dimensional in the 2θ direction: 2θ=0 to 35°, azimuth angle (chi)=-95 to -85° One-dimensional azimuth direction: 2θ=6.0~7.0°, azimuth angle (chi)=-180~0° After the X-ray diffraction measurement, the obtained diffraction image was converted into one dimension in the azimuth angle range of -180 to 0° in the range of 2θ = 6.0 to 7.0°, and the azimuth angle dependence of the diffraction intensity was confirmed. At this time, if a diffraction peak was observed at an azimuth angle of -90°, it was determined that the EVOH resin composition has a diffraction peak at 2θ = 6.0 to 7.0°.
[0107] [Gas barrier properties] The oxygen permeability of the obtained EVOH resin composition film was measured under conditions of 20° C. and 90% RH using an oxygen permeability measuring device (OX-TRAN100A, manufactured by MOCON).
[0108] [Table 1]
[0109] As can be seen from Table 1 above, the EVOH resin compositions of Examples 1 to 4, which contained EVOH (X) and a metal compound and satisfied formula (1), were excellent in gas barrier property under high humidity conditions. On the other hand, the EVOHs of Comparative Examples 1 and 3, which did not contain a metal compound, and the EVOH resin composition of Comparative Example 2 all had poor gas barrier properties.
[0110] In the above embodiment, specific embodiments of the present invention are shown, but the above embodiment is merely illustrative and should not be interpreted as being limiting. Various modifications that are obvious to those skilled in the art are intended to be within the scope of the present invention. [Industrial Applicability]
[0111] The EVOH resin composition of the present invention is useful as a packaging material, particularly as it has excellent gas barrier properties, particularly oxygen barrier properties, under high humidity conditions, and can be suitably used as a packaging material for foods, medicines, etc.
Claims
1. An ethylene-vinyl alcohol-based copolymer resin composition containing an ethylene-vinyl alcohol-based copolymer (X) and a metal compound, wherein the metal compound is a Zn-containing layered compound and satisfies the following formula (1): ΔA 2 =A 2 -A 2,0 >0 ・・・(1) (Above A 2 represents the second virial coefficient when the ethylene-vinyl alcohol copolymer resin composition is subjected to static light scattering measurement using hexafluoroisopropanol as a solvent, and A 2,0 Similarly, represents the second virial coefficient of the ethylene-vinyl alcohol copolymer (X) in the ethylene-vinyl alcohol copolymer composition.
2. The ethylene-vinyl alcohol copolymer resin composition according to claim 1, characterized in that the content of the metal compound in terms of metal is 0.01 to 10 parts by weight based on 100 parts by weight of the ethylene-vinyl alcohol copolymer (X).
3. 3. A film comprising the ethylene-vinyl alcohol copolymer resin composition according to claim 1.
4. The oxygen permeability of the above film under conditions of 20°C and 90% RH is 15cc・20μm / m 2 4. The film according to claim 3, characterized in that it has a viscosity of not more than 1.times.day.atm.
5. A multilayer structure comprising at least one layer of the film according to claim 3 or 4.
Citation Information
Patent Citations
Coating material and coated film using the same
JP2004091521A
Method for producing composition
JP2004323787A
Method of producing composite material
JP2012087215A
Resin composition containing ethylene-vinyl alcohol copolymer, laminate, and molded article
JP2017088666A
Ethylene - vinyl ester-based copolymer saponification product composition and production method therefor
WO2016088862A1